اتفاقية سايكس بيكو : السياق والتداعيات 1916 – 1923 "حول مستقبل كوردستان " - الجوادي, غسان ولید (Sulaimani Journal for Humanities, 2018)
Abstract Sykes- Picot Agreement which was held in 1916 is considered one of the most famous agreements in contemporary history. The causes of this agreement provided that the provinces of the ottoman state shall be divided between Britain, France and Russia. It also represents the imperialistic spirit in its ugliest form because these countries concluded this agreement for their own interests without paying attention to the rights of their peoples and their national ambition, moreover, geographical consideration or topographies or race were not taken into account. The agreement had also consequences represented by discussing the fate including of the peoples of the ottoman state including the Kurds. However, at the end these countries disregarded the ambition and the future of the Kurds regarding their self- determination.